Diseño para adecuación de la máquina de ensayos de impacto Charpy de la Universidad Antonio Nariño sede sur para la toma automática de datos (2020)
Taking into account the university's existing resources as laboratory equipment, which are wasted due to technological obsolescence or breakdowns and given the expressed need on the part of the FIMEB (School of Mechanical, Electronic and Biomedical Engineering) to leave the Charpy impact tests, as well as its installation in the materials laboratory of the Universidad Antonio Nariño, South headquarters, the project is being carried out for this purpose; providing the knowledge acquired in the courses taken (engineering in industrial and mechanical automation), a complete analysis of the machine, calculations and corresponding designs are carried out, with the technical and physical requirements necessary for the execution of tests on metal specimens and the automatic taking of the variables required for the analysis of the material. A set of components is delivered for the mechanical and physical adaptation necessary to fine-tune the existing structure, where the bearing and shaft are changed, adaptations for the installation of the lateral bases for mounting the control and movement elements, are the dashboard for automatic control of data acquisition with the respective programming guide and graphic interface is designed and put into operation, the elements for the motorization and brake of the machine pendulum are supplied, diagnostics for the bearings and elements involved in the movement of the same, design for the anchorage and protection enclosure for the operators and installation of the machine in the mechanical testing laboratory. Additionally, the respective laboratory guide for the Charpy test is provided, supporting documentation for the test records under the ASTM-E23 standard; together with the machine installation guide for its correct start-up